(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Poetry is concerned with the means and techniques that characterize poetic speech from ordinary speech. It expresses poetry in an intensive manner and with several techniques that perform an aesthetic function in the way of building technology on the one hand and its consistency with the entire text on the other hand, as well as adding to the meaning of exaggeration and influence. The first part dealt with the concept of poeticism, the second dealt with the characteristics of poetic language, and the second part dealt with the language of poeticism. Section III talks about the changes of the concept and its causes.